1999
DOI: 10.1046/j.1464-410x.1999.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Papillary renal cell carcinoma: clinicopathological characteristics and evaluation of prognosis in 42 patients

Abstract: Objective To determine the clinicopathological characteristics of histologically defined papillary renal cell carcinoma (RCC) in relation to prognosis. Patients and methods In total, 768 patients with RCC underwent nephrectomy at our university hospital between 1957 and 1995. RCC was classified into clear‐cell carcinoma in 689 patients (89.7%, no follow‐up in 14), chromophobe cell carcinoma in 36 (4.7%, no follow‐up in two) and papillary RCC in 43 (5.6%, no follow‐up in one). In the present study, the 42 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 17 publications
0
29
0
4
Order By: Relevance
“…In their study, the nuclear grade and the pathological stage were not predictive of the outcome. Onishi et al (15) confirmed also that the prognosis is better in basophilic tumors (Type 1) than in eosinophilic tumors (Type 2). In the present study, we have shown that Type 2 tumors are significantly associated with metastatic progression and a poorer survival rate than Type 1.…”
Section: Discussionmentioning
confidence: 89%
“…In their study, the nuclear grade and the pathological stage were not predictive of the outcome. Onishi et al (15) confirmed also that the prognosis is better in basophilic tumors (Type 1) than in eosinophilic tumors (Type 2). In the present study, we have shown that Type 2 tumors are significantly associated with metastatic progression and a poorer survival rate than Type 1.…”
Section: Discussionmentioning
confidence: 89%
“…3 Other than sporadic case reports, only a few studies of the clinicopathological features and the prognosis of PRCC have been conducted in Japan using the recent histological subclassification. Onishi et al 4 reported that the incidence of PRCC accounts for 5.6% of renal cell carcinomas, and Yamanaka et al 5 recently suggested that there were no differences in clinicopathological features (including prognosis) between type 1 and type 2 PRCCs; this finding is very different from those in previous reports. 2,[6][7][8] Given this background , we performed a retrospective examination of the clinical and pathological characteristics and prognosis of Japanese patients with PRCC.…”
Section: Introductionmentioning
confidence: 78%
“…Clinical characteristics, e.g. survival, sex ratio, stage and grade distribution, and clinical manifestations, differ where the subtype (variant) of RCC differs [16][17][18]. Therefore, each factor affecting the prognosis of RCC must be analysed and then stratified according to the subtype of RCC.…”
Section: Discussionmentioning
confidence: 99%